Carboxymethylinulin–Chitosan Nanoparticles for the Delivery of Antineoplastic Mitoxantrone. (5th October 2016) - Merli, Daniele; Pivi, Fabrizio; Profumo, Antonella; Quadrelli, Paolo; Milanese, Chiara; Risi, Giulia; Visai, Livia
Abstract: Mitoxantrone (MTX) is an antineoplastic agent whose use is limited by serious side effects on non‐neoplastic cells. The aim of this study was the development of a new drug release system using an ionotropic gelation technique for microencapsulation of MTX in chitosan–carboxymethylinulin nanoparticles (CCInp), followed by evaluation of their cytotoxic effects on neoplastic MDA‐MB‐231 and non‐neoplastic NIH3T3 cell lines. The CCInp were prepared through a new reliable method for easy functionalization of both inulin and chitosan. Both unloaded and drug‐loaded nanoparticles were characterized by transmission electron microscopy (TEM) and dynamic light scattering (DLS) and showed a spherical morphology with an average hydrodynamic diameter between 40 and 80 nm. Both nanoparticles were stable and easily degraded by lysozyme. MTX‐loaded nanoparticles led to a greater mortality of MDA‐MB‐231 relative to free drug due to the ability of the nanoparticles to accumulate preferentially in neoplastic cells. The developed drug release system retains the ability to kill MDA‐MB‐231 cells in vitro, improving the survival of NIH3T3 cells. Abstract : Nanoparticle novelty : A new drug release system was developed using an ionotropic gelation technique for microencapsulation of mitoxantrone in chitosan–carboxymethylinulin nanoparticles (MTXnp). Evaluation of their cytotoxic effects showed greater mortality of neoplastic cells relative to free drug, as MTXnp is preferentially accumulated in neoplastic cells and can overcome resistance to MTX.